2007
DOI: 10.1017/s1751731107702070
|View full text |Cite
|
Sign up to set email alerts
|

Key signalling factors and pathways in the molecular determination of skeletal muscle phenotype

Abstract: The molecular basis and control of the biochemical and biophysical properties of skeletal muscle, regarded as muscle phenotype, are examined in terms of fibre number, fibre size and fibre types. A host of external factors or stimuli, such as ligand binding and contractile activity, are transduced in muscle into signalling pathways that lead to protein modifications and changes in gene expression which ultimately result in the establishment of the specified phenotype. In skeletal muscle, the key signalling casc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 186 publications
1
26
0
Order By: Relevance
“…In animal production for meat, meat color and tenderness are closely associated with a predominance of red fibers (Chang, 2007). This study showed that porcine soleus muscle is redder than EDL muscle ( Figure 1A, B), and increased oxidative type I fibers in porcine soleus muscle were shown by immunohistochemical staining ( Figure 1C), in agreement with an earlier report (Lefaucheur et al, 2004).…”
Section: Muscle Fiber Composition In Porcine Soleus and Edl Musclessupporting
confidence: 91%
“…In animal production for meat, meat color and tenderness are closely associated with a predominance of red fibers (Chang, 2007). This study showed that porcine soleus muscle is redder than EDL muscle ( Figure 1A, B), and increased oxidative type I fibers in porcine soleus muscle were shown by immunohistochemical staining ( Figure 1C), in agreement with an earlier report (Lefaucheur et al, 2004).…”
Section: Muscle Fiber Composition In Porcine Soleus and Edl Musclessupporting
confidence: 91%
“…In search of potential downstream effectors of H19/let-7-mediated regulation during muscle differentiation, we focused our attention on insulin-like growth factors (IGF1 and IGF2), major regulators of pre- and postnatal muscle development and growth (Braun and Gautel, 2011; Chang, 2007). IGF1 and IGF2 act through the same receptor, IGF1R, to promote myogenesis (Braun and Gautel, 2011; Chang, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Narkar et al (2008) found that peroxisome proliferator-activated receptor d (PPARd) agonist can increase oxidative myofibres in adult mice, and CLA can act as a ligand for some of PPARs family, such as PPARa, g and d (Meadus et al, 2002;Bassaganya-Riera et al, 2004). Furthermore, Chang (2007) reported that PGC-1a activation, in partnership with nuclear hormone receptors, including PPARs, could increase oxidative capacity in skeletal muscle. These reports would provide some basis for further studies on the specific mechanism of CLA influencing muscle-fibre types.…”
Section: Discussionmentioning
confidence: 99%